DESIGN OF CONVEYOR FOR DRAINING FRYING PRODUCTS AND MIXING SKIN CRACKERS AT UMKM ADIARSA KARAWANG - Aditya, Ari (Universitas Muhammadiyah Semarang, 2024)
UKM Food Karawang is a small industry engaged in making leather crackers with the main raw material being cowhide. UKM which was founded in 2004 until now produces skin crackers. On this occasion, the author tries to analyse work productivity, effective and efficient use of work tools, because productivity is continuous with the use of simple and not yet representative tools, it is necessary to design work aids to improve productivity in UKM. One way to overcome efforts to increase productivity in UKM is to carry out an analysis of every production process that occurs in UKM. After that, it can be proposed what improvements need to be made to overcome productivity deviations. From the results of research conducted on cracker UKM, there are inefficient production work steps and the use of simple production equipment which can cause inefficiency in the production of skin crackers. A lot of liquid cooking oil was spilled and the cracker seasoning was mixed unevenly during the seasoning process. The potential for inefficiency found in each process at UKM Food Karawang is in the drying process, fur removal and skin cleaning, in the process of taking raw materials, boiling, draining, cutting, frying, packaging, and in the seasoning process. Based on research, the inefficient cracker production process occurs at the stage of the cooking oil draining process and the seasoning mixing process. Things that can cause inefficiency are work tools that are not effective when draining and crackers thatare not mixed evenly during the seasoning process, so it is recommended that companies improve the condition of work tools in order to minimize losses with draining tools in the form of conveyors and spice mixers that are mechanically designed. by paying attention to the dimensions of the work space in the process of frying and powdering crackers.